Hydroponics - A Novel Alternative For Geoponic Cultivation Of Medicinal Plants And Food Crops - MURALI MUGUNDHAN. R,; SOUNDARIA. M,; MAHESWARI. V,; SANTHAKUMARI. P,; GOPAL. V., (International Journal of Pharma and Bio Sciences, 2011)
The increased population, sub-urbanization of the forest (excluding land for commercial food production), improper agricultural practice which altered the soil pH, synthetic fertilizers, pesticides which drastically reduced the soil flora and fertility which made a quench for the new alternative technique for obtaining the food and medicinal plants of better quality, yield and for growing fresh produce in non-arable areas of the world. Consumption of herbal medicines is widespread and increasing. Harvesting from the wild, the main source of raw material is causing loss of genetic diversity and habitat destruction. Hydroponics was found to be better alternative and can be defined as the cultivation of plants without soil, which is being commercially used in the most of the western countries. This study explores the applications of this cultivation technique and to reveal its future importance. This technique can be adapted to almost all the terrestrial plants. Vegetable food crops like wheat, tomato, marijuana, dill and many more plants are being cultivated in commercial scale. The construction of a hydroponic system requires an initial investment, hard work, and care. Better the yield will be, if approached as it needs. It was recommended that this technique can be adapted as a step to produce the food crops and medicinal plants to meet the global demand, to control the global warming, and there by conserving the Mother Nature for the better future.